Energy efficiency strategies for railway application: alternative solutions applied to a real case study. Issue 2 (1st June 2018) - Alfieri, Luisa; Battistelli, Luigi; Pagano, Mario
Abstract : This study focuses on the topic of energy efficiency for railway application. A case study extrapolated from a real system was approached. An entire railway infrastructure, constituted by an alternating current (AC) primary grid, a direct current (DC) railway system and some AC/DC railway electrical substations (ESSs), was observed. The considered system was represented to study the operation of the railway infrastructure in terms of energy. A method, based on an AC/DC power flow approach, was formulated to calculate the efficiency in the use of electrical energy, during the motion of a fleet of trains. The method reports the solution vector (i.e. the AC and DC voltages and currents) as a function of the scheduling of the railway service. The results of the numerical simulations focused on the energy amounts at the ESS. The discussion gives evidence to the impact of alternative operating solutions in terms of energy efficiency strategies.